2020
DOI: 10.3892/etm.2020.9301
|View full text |Cite
|
Sign up to set email alerts
|

HIPK2 sustains inflammatory cytokine production by promoting endoplasmic reticulum stress in macrophages

Abstract: Uncontrolled inflammatory cytokine production by macrophages contributes to numerous conditions, including infection, endotoxemia and sepsis. A previous study proposed that endoplasmic reticulum (ER) stress acts as an essential process in inflammatory cytokine production by macrophages. The present study used a mouse sepsis model and in vitro macrophages to demonstrate that homeodomain-interacting protein kinase 2 (HIPK2) sustained cytokine production in an ER stress-dependent manner. HIPK2 expression was upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The previously reported that HIPK2 plays important role in inflammatory cytokine production [36]. In this work, the expression of HIPK2 was a prominent upregulation in RA tissues and cells.…”
Section: Discussionsupporting
confidence: 53%
“…The previously reported that HIPK2 plays important role in inflammatory cytokine production [36]. In this work, the expression of HIPK2 was a prominent upregulation in RA tissues and cells.…”
Section: Discussionsupporting
confidence: 53%
“…A recent study suggests that HIPK2 sustains inflammatory cytokine production by promoting endoplasmic reticulum stress in macrophages, which shows the decreased phosphorylation levels of p65 in LPS-stimulated Hipk2 knockdown PEMs (43). However, we did not observe significant changes of p65 phosphorylation after Hipk2 knockdown (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 54%
“…HIPK2 regulates PPM1D protein levels by inducing its degradation in DNA-damaged cells, triggering activation of the DNA repair pathway 133 . HIPK2 expression increases in LPS-stimulated macrophages, and its knockdown attenuates the expression of inflammatory cytokines 134, 135 . S46 is also a HIPK2 substrate.…”
Section: Discussionmentioning
confidence: 99%